2013
DOI: 10.1088/1478-3975/10/3/036010
|View full text |Cite
|
Sign up to set email alerts
|

Early signatures of regime shifts in gene expression dynamics

Abstract: Recently, a large number of studies have been carried out on the early signatures of sudden regime shifts in systems as diverse as ecosystems, financial markets, population biology and complex diseases. Signatures of regime shifts in gene expression dynamics are less systematically investigated. In this paper, we consider sudden regime shifts in the gene expression dynamics described by a foldbifurcation model involving bistability and hysteresis. We consider two alternative models, Models 1 and 2, of competen… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
40
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 25 publications
(40 citation statements)
references
References 44 publications
0
40
0
Order By: Relevance
“…Similar facilitation mechanisms appear in a vast variety of examples in population ecology (Allee effect) (19); neuroscience (synaptic facilitation) (20); systems biology (21); and, in general, climate, biological, and social sciences (1,22,23).…”
mentioning
confidence: 64%
See 2 more Smart Citations
“…Similar facilitation mechanisms appear in a vast variety of examples in population ecology (Allee effect) (19); neuroscience (synaptic facilitation) (20); systems biology (21); and, in general, climate, biological, and social sciences (1,22,23).…”
mentioning
confidence: 64%
“…Predicting and anticipating catastrophic regime shifts and distinguishing them from their smoother counterparts constitutes a timely subject with a vast number of important applications, including the prevention of biodiversity collapse or radical climate changes as the result of anthropogenic pressures (21,(29)(30)(31)(32). Indeed, early warning indicators of regime shifts (such as increasingly slower return rates from perturbation and rising variance) have been proposed, and some of them have been empirically tested (9,14,30,31), even if their degree of robustness and reliability is still under debate (33,34).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Theoretical and empirical studies have found that signatures of "critical slowing down" in the spatiotemporal dynamics may be used to indicate impending tipping points (18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29). These indicators are based on the fact that the dynamics around the equilibrium of a system slows down near a tipping point (19,30,31).…”
mentioning
confidence: 99%
“…While we will not delve into deeper detail why such changes may occur, the phenomenon of regime changes has been studied extensively in the fields of ecology [60,61,62], economy and finance [63,64,65,66,67], and biology [68,69]. Given the diversity of fields studying regimes, there is no general consensus of what a regime entails, nor its length or abruptness.…”
Section: Regime Changes and Gated Bayesian Networkmentioning
confidence: 99%